California State University, Channel Islands Foundation Financial Statements (With Supplementary Information) and Independent Auditor's Report (2023)
We have audited the financial statements of California State University, Channel Islands Foundation("Foundation"), a component unit of California State University, Channel Islands as of and for the yearended June 30, 2023, and the related notes to the financial statements, which collectively comprise theFoundation's basic financial statements as listed in the index.In our opinion, the accompanying financial statements present fairly, in all material respects, the financialposition of the Foundation as of June 30, 2023, and the changes in its financial position and its cash flowsfor the year then ended in accordance with accounting principles generally accepted in the United Statesof America.